Nickel uptake in hydroponics and elemental profile in relation to cultivation reveal variability in three Hypericum species - Kovacik, Jozef; Husáková, Lenka; Graziani, Giulia; Patočka, Jan; Vydra, Marek; Rouphael, Youssef (Elsevier France, 2022)
The Hypericum species (H. perforatum, H. olympicum, and H. orientale) were cultured in hydroponics with excess nickel (Ni, 1 or 100 mu M Ni) to compare the metallic and metabolite content. Identical species were collected outdoor to assess the same parameters (including uranium and lanthanides) with total of 53 elements. The results showed that Ni was less accumulated in shoots in hydroponics (translocation factor of 0.01-0.25) and the highest absolute amount was detected in H. olympicum. Essential elements were typically depleted by Ni excess, but Co and Na increased. Soluble phenols, sum of flavonols and catechin rather increased in response to Ni but quercetin glycosides and free amino acids decreased in the shoots of H. olympicum mainly. Comparison of laboratory and outdoor growing plants showed more phenols in outdoor samples but not in H. olympicum and individual metabolites differed too. Plants cultured in hydroponics contained lower amount of non-essential, toxic and rare earth elements (30-100-fold) and shoot bioaccumulation factor in outdoor samples was low for most elements (<0.01) but not for Cd and Pt. Data reveal that H. olympicum is a potent source of phenolic metabolites whereas H. orientale accumulates many elements (38 out of 53 elements).
Příjem niklu v hydroponii a elementární profil ve vztahu ke kultivaci odhalují variabilitu u tří druhů Hypericum
Keywords: bioremediation; heavy metals; medicinal plants; phenolic metabolites; rare earth elements; bioremediace; těžké kovy; léčivé rostliny; fenolické metabolity; prvky vzácných zemin